Translating African Names in Fiction - Bariki, Isaiah (Íkala, Revista de Lenguaje y Cultura, 2009)
In this paper, we study the sociocultural and ethno-pragmatic significance of African names as used by the Yoruba and Izon of Nigeria and the Akan of Ghana. From the perspective of linguistic anthropology, we show the non-arbitrary nature of these names and demonstrate the need to translate them, particularly in fictional texts, so that their significance may be preserved. Received: 25-11-08 / Accepted: 07-07-09 How to reference this article: Bariki, I. (2009). Translating African Names in Fiction. Íkala. 14(3), pp.43-61